The End of Empire in the Middle East: Britain's Relinquishment of Power in Her Last Three Arab Dependencies by Glen Balfour-Paul. Cambridge, UK: Cambridge University Press, 1991, xxiii + 198 pp. (American Journal of Islam and Society, 1996)
Living memory has now faded concerning the scattered pieces ofempire that Britain ruled in East Africa and South and East Arabia for upto a quarter of a century after the end of the Second World War. In the nottoo-distant future, what Elizabeth Monroe once described felicitously asBritain's "moment" in the Middle East will have passed from personal recollectioninto history. Mindful of that inevitability, British diplomat andquondam scholar Glen Balfour-Paul has undertaken to chronicle the postwarencounter between Britishers and Arabs in Sudan, Aden, and the Gulfstates from which Britain withdrew in 1956, 1967, and 1971, respectively.The results of his study should be of particular interest to government officialsrequiring perspective for the formulation of policy and to neophyteforeign service officers about to depart for the regions discussed, as well asto scholars and advanced students of the contemporary Middle East.To his subject, Balfour-Paul brings almost unique credentials. Afterexperience in the Middle East during the Second World War, he became amember of the Sudan Political Service for nine years and, thereafter, servedas a diplomat until 1977 in various Arab countries, in three of them asambassador. The book under review was written largely in the late 1980swhile the author was an honorary research fellow at the Centre for ArabGulf Studies at Exeter University. In the meticulousness of its research, theobjectivity demonstrated on contested issues, and above all in the eleganceof its prose, the volume at hand is a model of what diplomatic history (acraft now rarely practiced by professional historians) should be. Those onboth sides of the British-Arab divide have reason to be grateful that there is ...